Effectivity of the Mathematics Learning Model ICCACRE in Developing Mathematics Creativity of Junior High School Students. Issue 1 (May 2021) - Alimuddin,; Ruslan,; Nashrullah,
Abstract: ICCACRE stands for Interaction, Connection, Collaboration, Application, Creativity, Reflection, and Extension. The seven words consecutively refer to the syntax of the mathematics learning model called ICCACRE. It is actually the result of the developmental research referring to the theory of development of Plomp. The theory contains five stages of development, Those are preliminary investigation, designing, realization, giving test evaluation and revision, and implementation. In the implementation or limited trial stage, it was conducted an experimental research to investigate the effectivity of the model in developing mathematics creativity of junior high school students. Students from class VIII-2 were selected as participants in this study based on the selection with cluster random sampling technique from all students class VIII of SMPN 27 Makassar for 2019-220. Mathematical creativity data were obtained using the mathematical creativity test developed by the researcher referring to the creative indicators: fluency, flexibility, and originality which was equipped with an assessment rubric. The collected data were analyzed with descriptive statistics to explore mathematical creativity in detail. Meanwhile, inferential analysis is used to see the effectiveness of the model in developing students' mathematical creativity. The results showed that the students' fluency was in the high category. Meanwhile, the flexibility and originality of students are included in the medium category. Normalized N-Gain mean. indicates that fluency and flexibility increase in high category. Is increasing originality in the medium category. Furthermore, the results of the infrential analysis show that the ICCACRE model is effective in developing the mathematics creativity of junior high school students.